Attending work with chronic pain is associated with higher levels of psychosocial stress - Greig Adams; Tim V. Salomons (Taylor & Francis Group, 2021)
Background and Aims: Much is known about the impact of pain in terms of medical costs and missed work. Less is known about its associations when individuals are present for work. This study examines "presenteeism" by analyzing the psychosocial costs of pain in the workplace, using the 2015 European Working Conditions Survey (EWCS). Methods: We conducted cross-sectional analysis of 2384 individuals with chronic pain and 2263 individuals without pain (matched by age and sex) using data from the 2015 EWCS. We compared groups in terms of the following psychosocial factors: supervisor support, job responsibility, team cohesion, discrimination, threats/abuse, job competency, job reward, sexual harassment, stress, and job security. The groups were also compared in terms of days lost due to illness. Results: People with pain were 64% less likely to view their job as rewarding (odds ratio [OR] = 0.61; 95% confidence interval [CI], 0.57-0.65), 47% more likely to be subjected to threats/abuse in the workplace (OR = 0.68; 95% CI, 0.63-0.73), 30% more likely to report poor supervisor support (OR = 0.77; 95% CI, 0.73-0.82), and 28% more likely to perceive discrimination in the workplace (OR = 0.78; 95% CI, 0.71-0.85). People with pain missed approximately nine more days of work per year than respondents without pain. Conclusions: Chronic pain was associated with lower vocational fulfillment and feelings of being ostracized in the workplace. These findings suggest that the presence of pain in the workplace goes well beyond lost productivity due to absenteeism.